Benefits of Roller Derby: The Roller Girl Perspective (Department of Physical Education, Sport, Health and Recreation, 2018)
Roller derby consists of two teams vying for points played on a flat oval track wearing quad skates. The specific research questions asked were: What are the characteristics of roller derby league members? What are the motivations of women who join roller derby leagues? What are reasons for continuing to participate? Do roller derby participants identify specific characteristics of the sport that distinguish it from other sports? Are there specific benefits from roller derby women seek and receive? An on-line survey was used and qualitative data were analyzed (n=1597). Based upon the data, a typical respondent is Caucasian, 20 to 40 years of age, heterosexual, in a married/domestic partnership, and has a post-secondary degree. Reasons for joining included looking for a new way to get exercise, add something new and different to my life, and roller derby might fit my personality. For continuing, the following reasons were ranked as important; roller derby adds richness to my life, I like the idea of overcoming obstacles as a team, and I like the social interaction. Because of participation, they benefited several ways including a positive opinion of self, health improvement, increased relationships, and an added outlook.